Determinação dos intervalos de referência para lipídios, lipoproteínas e apolipoproteínas no estado do Rio Grande do Norte - Fernandes, Luzia Leiros de Sena (2009)
The lipid profile is a group of lab tests that include triglycerides, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). However, serum non-HDL-C, Apo A-I and Apo B levels, as well as the lipids ratios (TC/HDL-C, LDL-C/HDL-C and Apo B/Apo A-I), have been described as better predictors of cardiovascular diseases. Reference intervals are tools often used to help the evaluation of the people s health state. These days, Brazilian studies still use the reference intervals of lipids and lipoproteins from other countries, ignoring differences between the populations. Therefore, this study aimed to establish reference intervals for lipids, lipoproteins and apolipoproteins in adults of Rio Grande do Norte/Brazil. Healthy individuals (96 men and 283 women) between 18 and 59years old formed the reference sample group. The samples were collected after fasting 12 to 14 hours. Information on lifestyle and dietary habits of the participants were obtained through questionnaire. The serum glucose level and renal and liver activity were evaluated by laboratory testing. The results of lipid profile were analyzed according to sex, age and mesoregion of Rio Grande do Norte, with significance level of 5% (p < 0,05). The lower and upper reference limits were identified by the 2.5 percentile and 97.5 percentile, respectively, and assurance intervals of 90% was calculated for each of these limits. Among the determinants of lipid profile analyzed, only a few significant differences were observed according to sex, but in terms of age, the groups of smaller and older ages were most likely different. When evaluated by region, the means of West region shown the most significant variations. Not many studies were useful to compare the reference intervals determined in this study. Thus, it becomes necessary to carry out similar studies in other regions of Brazil and of the world given the clinical importance of reference intervals